Novel amphiphilic conetworks based on compatibilized NBR/SBR–montmorillonite nanovulcanizates as membranes for dehydrative pervaporation of water–butanol mixtures. Issue 7 (24th July 2013) - Essawy, Hisham; Tawfik, Magda; El‐Sabbagh, Salwa; El‐Gendi, Ayman; El‐Zanati, Elham; Abdallah, Heba
<x xml:space="preserve">Abstract</x> Nanocomposite vulcanizates comprising the poorly compatible acrylonitrile butadiene rubber/styrene butadiene rubber blend are homogenized with 20 parts per hundred montmorillonite forms showing various levels of amphiphathicity: slightly hydrophobic (Mont‐25/50) and highly hydrophobic (Mont75/100) as compared to the highly hydrophilic pristine form (Mont‐0). The purpose of the amphiphathicity is to afford simultaneous binding sites for the poorly compatible components. Thus maximum compatibility is reached with either Mont‐75 or Mont‐50 which improves the mechanical properties. Scanning electron microscopy corroborates cocontinuous morphology. Water vapor permeation through sheets/membranes fabricated from these compositions follows best performance with Mont‐25 followed by Mont‐50 while Mont‐75 and Mont‐100 based membranes acquire an organized continuous drop. This highlights the role of organophilicity in dominating the morphology and performance in pervaporation application. Dehydration of butanol is effective using such membranes with superiority for Mont‐25 based membrane. A plausible model for the transport mechanism was proposed and supported by activation energy calculations for the permeation of the individual components and the sorption affinity measurements as well. All these parameters together suggest the arrest of the n‐butanol within the macrmolecular chains of the membranes, favored by its chemical affinity. This allows therefore a passageway for the water to cross to the other side of the membrane through plasticization of the chains and creation of free volumes which is known as solution diffusion mechanism. POLYM. ENG. SCI., 54:1560–1570, 2014. © 2013 Society of Plastics Engineers